“What’s Next?” Jasper Fforde’s Attempts on Jane Eyre - Wolfgang Funk (Revue LISA)
This article attempts to analyse the interplay of Jane Eyre with one of its most daring re-appropriations, Jasper Fforde’s 2001 novel The Eyre Affair, which will be presented as a ‘parallolotopia’ in this essay. The main focus is on the inter-textual relationship between the two texts and the interplay and entanglement of the two novels will be analysed as a particular form of post-modern pastiche (in the sense of Fredric Jameson), the main characteristic of which is its self-reflective attitude. This pastiche does not only disestablish traditional role allocations in the framework of literary communication (such as author, story and reader), it also might serve as a completely new paradigm in the relation of literature and its perception, who which (as the article attempts to point out) will be grounded in an ‘aesthetics of insolence’ rather than one of diffidence, as was traditionally the case.